Trend and Patterns of Research Proposals Submitted for Ethical Review in Nepal Health Research Council
Background: The characteristics of research proposals submitted to the Nepal Health Research Council reflect the trend of health-related researches being conducted in Nepal. The objective of the study was to analyze research proposals submitted for the ethical review in Nepal Health Research Council from 2017 to 2019. Methods: A retrospective record review of research proposals received over three years from 2017 to 2019 were analyzed. A total of 2,305 research proposals was included in the study. The number of research studies per year, types of study design, priority area of research, and rejected proposal were the intended variables for the study. Results: 91.45% (503), 92.19% (748), and 755 (80.1%) of received proposals were approved from Ethical Review Board in 2017, 2018 and 2019. The number of research proposals increased every year (550 in 2017, 812 in 2018, and 943 in 2019). Among the approved proposals non-communicable disease (n=150;15.90%) in 2019